2006
DOI: 10.1107/s1600536806003606
|View full text |Cite
|
Sign up to set email alerts
|

L-Tyrosinen-butyl ester

Abstract: The title compound, C13H19NO3, adopts a folded conformation. Mol­ecules are connected into a three‐dimensional array via O—H⋯N and N—H⋯O hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For L-TBE, there are three weak hydrogen bonds between the N-H 2 and oxygen atoms in adjacent C(9) chains [27], whereas only two are observed for L-TME and L-TEE.…”
Section: C-háááo and Weak N-háááo Hydrogen Bondsmentioning
confidence: 95%
See 1 more Smart Citation
“…For L-TBE, there are three weak hydrogen bonds between the N-H 2 and oxygen atoms in adjacent C(9) chains [27], whereas only two are observed for L-TME and L-TEE.…”
Section: C-háááo and Weak N-háááo Hydrogen Bondsmentioning
confidence: 95%
“…Eventually, also the structure of D-Tyr was deposited in the Cambridge Structural Database [24,25]. Tyrosine alkyl esters received less attention, but the crystal structures for a number of them and some salts have been determined: D-tyrosine ethyl ester (D-TEE) [26], L-tyrosine n-butyl ester (n-butyl (S)-2-amino-3-(4-hydroxyphenyl)propionate) (L-TBE) [27], L-tyrosine methyl ester hydrochloride (L-TMEÁHCl), and one of its solvates (L-TMEÁHClÁCH 3 OH) [28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the adoption of this conformation, there is no evidence for significant intramolecular C-H•••π interactions. In terms of geometric parameters and overall conformation, the structure of (I) resembles that of the n-butyl analogue (Qian et al, 2006). Hydrogen bonding plays a significant role in stabilizing the crystal structure; see Table 1 for geometric parameters and symmetry operations.…”
Section: S1 Commentmentioning
confidence: 99%
“…For information about tyrosine alkyl esters as prodrugs and the structure and intermolecular interactions of l-tyrosine methyl ester compared to l-tyrosine and its ethyl and n-butyl esters, see: Nicolaï et al (2011). For the n-butyl analogue, see: Qian et al (2006). For macrocyclization of tyrosine alkyl esters with formaldehyde, see: Quevedo & Moreno-Murillo (2009); Nuñ ez-Dallos et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…In addition, they are hydrolyzed under physiological conditions (Nicolaï et al, 2011). The crystal structures for a number of tyrosine esters have been determined: methyl, ethyl (Nicolaï et al, 2011) and n-butyl esters (Qian et al, 2006). Previous computational and spectroscopic studies of L-tyrosine isopropyl ester have suggested that the macrocyclization process with formaldehyde can be explained by the formation of a template in solution through intermolecular hydrogen bonds between the amino and the phenolic hydroxyl groups on adjacent molecules of L-tyrosine derivatives (Quevedo & Moreno-Murillo, 2009;Nuñez-Dallos et al, 2012).…”
Section: L-tyrosine Isopropyl Estermentioning
confidence: 99%